Apparent and standardised ileal digestibility of amino acids in wheat, triticale and barley for broiler chickens at two different ages. Issue 1 (2nd January 2020) - Szczurek, W.; Szymczyk, B.; Arczewska-Włosek, A.; Świątkiewicz, S.
ABSTRACT: 1. The influence of the age of broiler chickens on ileal amino acid (AA) digestibilities in three cereals was examined. The digestibility estimates, including both apparent (AID) and standardised (SID) coefficients, for wheat, triticale and barley samples were determined using 14 and 28 d old broilers of mixed sex, fed diets containing the test grains as the only source of protein. 2. Each assay diet was offered to five replicate cages of 14 and eight birds respectively, for the 14 and 28 day samplings. On both sampling days, the contents from the lower half of the ileum were collected for determination of the AID coefficients. The SID coefficients were calculated using ileal endogenous amino acid (EAA) losses previously determined from birds fed an N-free diet. 3. The average AID for essential AA (EAA) in triticale and barley were significantly higher at 28 day compared to those at 14 days. In contrast, the magnitude of AID coefficients of AA in wheat was found to be in larger in the younger chickens. 4. Correction of AID for EAA losses increased the values of digestibility coefficients by an average of about 7%. The SID values of AA in wheat was not influenced by the age of broilers. The SID of most AA in triticale, and of all the AA in barley, were higher in 28-day-old chickens compared with their 14-day-old counterparts. The results suggested that the SID coefficients of EAA in wheat determined at day 28 could be applied to feed formulations for 14-day-old broilers, but in the case of triticale and barley, the values obtained in older chickens were not applicable in younger birds and vice versa .